Bioactive phenolic acids from Scorzonera radiata Fisch. - Tsevegsuren, N; Proksch, P; Wang, Y; Davaakhuu, G (Mongolian Journal of Chemistry, 2014)
Chromatographic separation of the crude extract obtained from the aerial parts of the Mongolian medicinal plant Scorzonera radiata yielded five new dihydrostilbenes [4], two new flavonoids, one new quinic acid derivative, as well as twenty known compounds including eight quinic acid derivatives, four flavonoids, two coumarins, five simple benzoic acids, and one monoterpene glycoside. We present here results on isolation and structural identification some active phenolic compounds from the Scorzonera radiata - eight quinic acid derivatives (quinic acid, 4,5-dicaffeoylquinic acid, 4,5-dicaffeoyl-epi-quinic acid, 3,5-dicaffeoylquinic acid, 3,5-dicaffeoyl-epi-quinic acid, chlorogenic acid, 5-p-coumaroylquinic acid (trans), 5-p-coumaroylquinic acid (cis)). Quinic acid derivatives exhibited antioxidative activity. DOI: http://dx.doi.org/10.5564/mjc.v12i0.177 Mongolian Journal of Chemistry Vol.12 2011: 78-84